A New Insight on Stereo-Dynamics of Penning Ionization Reactions - Falcinelli, Stefano; Pirani, Fernando; Candori, Pietro; Brunetti, Brunetto G.; Farrar, James M.; Vecchiocattivi, Franco (Frontiers in Chemistry, 2019)
Recent developments in the experimental study of Penning ionization reactions are presented here to cast light on basic aspects of the stereo-dynamics of the microscopic mechanisms involved. They concern the dependence of the reaction probability on the relative orientation of the atomic and molecular orbitals of reagents and products. The focus is on collisions between metastable Ne*(3P2,0) atoms with other noble gas atoms or molecules, for which play a crucial role both the inner open-shell structure of Ne* and the HOMO orbitals of the partner. Their mutual orientation with respect to the intermolecular axis controls the characteristics of the intermolecular potential, which drives the collision dynamics and the reaction probability. The investigation of ionization processes of water, the prototype of hydrogenated molecules, suggested that the ground state of water ion is produced when Ne* approaches H2O perpendicularly to its plane. Conversely, collisions addressed towards the lone pair, aligned along the water C2v symmetry axis, generates electronically excited water ions. However, obtained results refer to a statistical/random orientation of the open shell ionic core of Ne*. Recently, the attention focused on the ionization of Kr or Xe by Ne*, for which we have been able to characterize the dependence on the collision energy of the branching ratio between probabilities of spin orbit resolved elementary processes. The combined analysis of measured PIES spectra suggested the occurrence of contributions from four different reaction channels, assigned to two distinct spin-orbit states of the Ne*(3P2,0) reagent and two different spin-orbit states of the ionic M+(2P3/2,1/2) products (M = Kr, Xe). The obtained results emphasized the reactivity change of 3P0 atoms with respect to 3P2, in producing ions in 2P3/2 and 2P1/2 sublevels, as a function of the collision energy. These findings have been assumed to arise from a critical balance of adiabatic and non-adiabatic effects that control formation and electronic rearrangement of the collision complex, respectively. From these results we are able to characterize for the first time, according to our knowledge, the state to state reaction probability for the ionization of Kr and Xe by Ne* in both 3P2 and 3P0 sublevels.